Body composition in sport, exercise and health (Routledge, 2013)
The analysis of body composition (fat, bone and muscle) is an important process throughout the biomedical sciences. This is the first book to offer a clear and detailed introduction to the key methods and techniques in body composition analysis and to explain the importance of body composition data in the context of sport, exercise and health.